Utilizing Spirulina in Combination with Concentrated Solar Thermal Technology for Sustainable Biofuel Production and Enhancing Cultivation Efficiency - A Review (International Journal of Food and Nutritional Sciences, 2022)
Biofuels reduce greenhouse emissions by 30-50% when compared with fossil fuels. However, nearly half of the biofuels have greater environmental costs than petrol. So, it is needed to have new cost effective and eco-friendly technology for fulfill of our energy demand. Solar energy, the most abundant and exploitable renewable energy resource is regarded as a major energy source for the future. Nevertheless, solar irradiation is characterized by relatively low energy density, intermittency and uneven distribution. Storage of solar energy for usage during non-solar times is required to match supply and demand rates in today‟s society. In this context, the application of solar energy for converting into storable, transportable, and energy-dense fuels (i.e., solar fuels) is an attractive option, with the advantage of contributing to promoting the commercialization of solar power technologies. This narrative review aims to describe and delineated on comprehensive summary of solar assisted Spirulina cultivation for biofuel production, including concentrating solar thermal technology and strategies to enhance the cultivation of spirulina.